Environmental and Social Injustices in East Africa: A Critique of the Modernization Approach to Environmental Communication - Jjuuko, Margaret (Rwanda Journal of Social Sciences, Humanities and Business, 2021)
The existing environmental injustices in the world have often been linked to industrialisation and modernisation of nations. In a bid to develop and modernise their nations, East African governments have adopted neoclassical developmentalist ideals of 'modernization' and 'capital investments‘, which largely involve exploitation of natural and human resources. The consequence is rampant and severe environmental degradation and related impacts in the region. While environmental degradation impacts affect all people residing in the region, the poor are hit hardest since they do not have ways to deal with disasters; hence, it becomes an environmental and a social justice issue. Although mass media are viewed as change agents and key players in the development agenda, and are often tasked to communicate information as widely as possible, these have adopted hierarchical and top down approaches to environmental and social justice issues and, in the process, helped to deepen the existing inequalities in society. From perspectives of Development Communication, this article critiques modernization discourses to development including: 'Top-down experts of development‘, 'Blaming the victim‘ and 'Social Darwinism‘. The purpose is to demonstrate how the East African media deploy this framework to (mis)represent environmental issues leading to aggravated environmental and social injustices in these societies. The article argues for a 'solution journalism approach‘ to environmental communication, whereby media as advocates of development, focus more on the contextual factors within which environmental issues and problems transpire.
Keywords: Environmental and social injustices; Communication for Development; Modernisation discourses; Solution journalism